Diverse nitrogen enrichments enhance photosynthetic resistance of Sargassum horneri to ultraviolet radiation - Li, Baoqi; Xu, Zhiguang; Jiang, Xiaotong; Wu, Hongyan; Bao, Menglin; Zang, Shasha; Yan, Fang; Yuan, Tingzhu (Frontiers in Marine Science, 2024)
In recent years, golden tides caused by floating Sargassum have induced severe ecological disasters globally. Eutrophication is a significant factor contributing to the massive spread of Sargassum golden tides. Furthermore, the thalli of Sargassum that float on the ocean surface are subjected to more ultraviolet radiation (UVR). The coupled impact of eutrophication and UVR on the photosynthetic physiology of golden tide species remains unclear. In this study, the thalli of Sargassum horneri, known to cause golden tide, were cultured and acclimated to three distinct nitrogen (N) conditions (natural seawater, NSW; NH4+-N enrichment; and NO3–N enrichment) for 6 days. Subsequently, the thalli were exposed to two different radiation treatments (photosynthetically active radiation (150 W m-2), PAR, 400–700 nm; PAR (150 W m-2) + UVR (28 W m-2), 280–700 nm) for 120 min, to investigate the photosynthetic effects of UVR and N on this alga. The findings demonstrated that exposure to UVR impeded the photosynthetic capacity of S. horneri, as evidenced by a decrease in the maximum photochemical quantum yield (Fv/Fm), photosynthetic efficiency (α) and chlorophyll content. Under diverse N-enrichment conditions, the alga tended to adopt various strategies to mitigate the adverse effects of UVR. NH4+-enrichment dissipated excess UVR energy through a greater increase in non-photochemical quenching (NPQ). While NO3–enrichment protected alga by enhancing N assimilation (higher nitrate reductase activity (NRA) and soluble protein content), and maintained a stable energy captured per unit reaction center for electron transfer (ET0/RC) and a higher net photosynthetic rate. Although different N enrichments could not completely offset the damage caused by UV radiation, they secured the photoprotective ability of S. horneri in several ways.